IMPLEMENTATION OF SINGLE NATIONAL CURRICULUM 2020 DEMOCRATIC VALUES PRACTICES AT ELEMENTARY SCHOOLS LEVEL IN PUNJAB (Contemporary Journal of Social Science Review, 2025)
The current study was designed to analyze Single National Curriculum (SNC) 2020 to determine teachers’ democratic values practices at the elementary level in Punjab. The study was descriptive and survey design was used to explore democratic values.  The sample of 300 respondents was selected through a simple random sampling technique from Lahore Punjab. The self-constructed questionnaire for students on teachers’ democratic values practices was employed to collect data from 6th, and 7th grade students to reveal teachers' democratic values practices in the classrooms. The reliability was confirmed by calculating Cronbach’s Alpha scores; .889. The collected data were analyzed employing mean, standard deviation, and independent samples t-tests were used to explore difference among teachers gender. The results of the study showed that teachers were more used to explanatory practices and critical thinking practices were less in practice. Findings further revealed a significant difference between teachers' democratic values practices in terms of teachers' gender and the school’s locality. Male teachers were practicing more democratic practices as compared to female teachers and teachers working in urban schools were practicing more democratic practices as compared to teachers teaching in rural schools. Findings further revealed significant differences between teachers’ democratic values practices teaching in 6th, 7th, and 8th grades. It is recommended that teachers may provide a democratic environment for learners to practice democratic values through explanatory, participatory, and critical thinking practices. Teachers' training institutions develop curriculum based modules on democratic values provided in the SNC of English and History content to enhance democratic values practices.